Affected and fundamental transactions: balancing the competing rights and interests of stakeholders envisaged in the Companies Act 71 of 2008 - Botha, Monray Marsellus (University of Pretoria, 2021)
Mini Dissertation (LLM (Corporate Law))--University of Pretoria, 2020.